1999
DOI: 10.1176/ps.50.5.674
|View full text |Cite
|
Sign up to set email alerts
|

Housing Placement and Subsequent Days Homeless Among Formerly Homeless Adults With Mental Illness

Abstract: Although consumers more frequently prefer independent living, placement in staffed group housing resulted in somewhat fewer days homeless for some groups of consumers. Further experience of homelessness by formerly homeless mentally ill individuals may be reduced by providing effective substance abuse treatment and by paying special attention to consumers identified by clinicians to be at particular risk for housing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
125
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 35 publications
2
125
0
2
Order By: Relevance
“…4 Clinical services for this population have included (1) community outreach, 5 (2) case management, [6][7][8] and (3) housing assistance involving either time-limited halfway house treatment 9,10 or longerterm mainstream community housing with support. 11,12 Recently, experimental studies [6][7][8][9][10][11][12][13][14] have demonstrated superior outcomes for diverse interventions, typically described as supported housing programs in which case management and housing resources are combined, with benefits more often demonstrated for housing outcomes than for clinical status. 15 Although no paradigmatic standards for this approach have emerged, it received a strong endorsement from the congressionally appointed Bipartisan Millennial Housing Commission.…”
mentioning
confidence: 99%
“…4 Clinical services for this population have included (1) community outreach, 5 (2) case management, [6][7][8] and (3) housing assistance involving either time-limited halfway house treatment 9,10 or longerterm mainstream community housing with support. 11,12 Recently, experimental studies [6][7][8][9][10][11][12][13][14] have demonstrated superior outcomes for diverse interventions, typically described as supported housing programs in which case management and housing resources are combined, with benefits more often demonstrated for housing outcomes than for clinical status. 15 Although no paradigmatic standards for this approach have emerged, it received a strong endorsement from the congressionally appointed Bipartisan Millennial Housing Commission.…”
mentioning
confidence: 99%
“…Both Goldfinger et al (1999) and Dickey et al (1996) report on an initiative that provided two types of housing in Boston for homeless persons with mental illness: independent apartments with communitybased services and so-called evolving consumer households, where the tenants lived communally and with gradually diminishing levels of staff assistance. Three-quarters of the total subjects were stably housed at the end of the 18-month follow-up period.…”
mentioning
confidence: 99%
“…Three-quarters of the total subjects were stably housed at the end of the 18-month follow-up period. The subjects in the group homes had fewer days homeless than the supported housing group, but otherwise no significant differences in housing outcomes or services use were found (Dickey et al 1996;Goldfinger et al 1999). …”
mentioning
confidence: 99%
“…The same authors also noted that mental disorders and substance abuse can follow homelessness in young people with "bidirectional processes underlying the link between drug use and homelessness such that the presence of one may predispose an individual to the other" ( [11] p. 470). Similarly, effective substance abuse treatment may assist in reducing homelessness [12] and providing housing for those homeless with major mental disorders may benefit their cognitive functioning [13].…”
Section: -John Howard Paynementioning
confidence: 99%